2014
DOI: 10.5539/ies.v7n2p10
|View full text |Cite
|
Sign up to set email alerts
|

Oral Academic Discourse Socialisation: Challenges Faced by International Undergraduate Students in a Malaysian Public University

Abstract: This paper reports a qualitative study which examines the challenges faced by six international undergraduate students in their socialisation of oral academic discourse in a Malaysian public university. Data were collected employing interviews. Students' presentations were also collected. Semi-structured interviews were transcribed verbatim and qualitative content analysis was employed to examine the challenges faced by international undergraduate students in their socialisation of oral academic discourse. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
(29 reference statements)
2
12
0
Order By: Relevance
“…feel anxious and uncomfortable because I find difficult vocabulary." This finding is in line with Kheirzadeh and Tavakoli (2012); Mahfoodh (2014) who reveal that one of the difficulties faced by master students in academic reading is an advanced level of vocabulary. Despite the difficulty faced by P1, he has an effective strategy to overcome his negative feeling.…”
Section: Affectivesupporting
confidence: 87%
“…feel anxious and uncomfortable because I find difficult vocabulary." This finding is in line with Kheirzadeh and Tavakoli (2012); Mahfoodh (2014) who reveal that one of the difficulties faced by master students in academic reading is an advanced level of vocabulary. Despite the difficulty faced by P1, he has an effective strategy to overcome his negative feeling.…”
Section: Affectivesupporting
confidence: 87%
“…In other words, the audience anxiety leads to "fear, tension and [they become] disorganised in front of an audience" (Buss, as cited in McCroskey, 2010, p. 146). Similar findings on anxiety during oral presentations were obtained by other researchers Kakepoto, Habil Omar & Said, 2012;Mahfoodh, 2014). A possible reason for the nervousness is their fear of negative evaluation; they are too concerned "about being judged despairingly or hostilely by others" (Carleton et al, 2006, p. 297).…”
Section: Discussionsupporting
confidence: 74%
“…Two students mentioned in their interviews that they were not able to speak English as fluently as Malay or their mother tongues. Elsewhee, El Enein (2011), Mahfoodh (2014) and Nguyen Thi Van (2010) also found that students who faced linguistic difficulties such as oral proficiency, fluency and lack of vocabulary and structures would be constrained in expressing their complex concepts and ideas when they were giving oral academic presentations. Thus, the students became highly apprehensive when they were required to deliver their presentation in English, and this emotion affected their performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Puvaneswary (2016) employed the 'Pecha Kucha' (PK) or 'chitchat' Japanese style of PPT presentation to enhance oral presentation skills among university students and findings indicated the PK style though successful was challenging for the low proficiency level students. Students also have difficulty in preparing PPT slides and organizing content in slides (Mahfoodh, 2014). Thus, learners should be taught the skills in preparing and delivering PPT oral presentations.…”
Section: Visuals In Aopmentioning
confidence: 99%